ADOPSITEKNOLOGI DAN INDEK PERTANAMAN POLA USAHA TANI BERBASIS LADA DI NANGABULIK KALIMANTAN TENGAH - SYAFRIL KEMALA (Pusat Penelitian dan Pengembangan Perkebunan, 1999)
Technology adoption and crops index ofpepper basedfarm¬ ing system in Nangabulik Central KalimantanA research on technology adoption, technology demontration and crops index of pepper based farming system was conducted in UPT Nangabu¬ lik, Central Kalimantan by using survey method. The purpose of the research was to show : (a) the role of technology demontration in increasing the willingness of the fanners in adopting the technology; (b) the crops index of the pepper based farming system as an indicator for income level. The data were analyzed by using nonparametics Wilcoxon sign rank test and cropping intencity index (CII). The results showed that the technology demontration of pepper based farming system had a significant effect in increasing the willingness of the farmers in adoption the technology. So that, the develop¬ ment of the pepper based farming system in IP I Nangabulik would go faster. An economic of scale aea of the pepper based farming system in Nangabulik would be achieved in around two years. The crops index of the pepper based fanning system was 215.30% meaning the level of eiciency of the pepper based farming system in using the land was 215.30% higher than the traditional farming system in Nangabulik. In other words the pepper based farming system would incease the farmers income by 215.30% (ceteis paibus). Compaing with the land in Java cropped with paddy and had crops index of 300% the pepper based farming system in Nangabulik would give higher income to the farmers after 5 years.